A revised fit of East and West Gondwanaland - Powell, C. Mc A; Johnson, B. D.; Veevers, J. J. (Tectonophysics, 1980)
Recently available evidence provides the basis for a revised fit between East and West Gondwanaland before break-up in the Late Jurassic: deep-sea drilling shows that the entire Falkland Plateau is probably underlain by continental crust, marine geophysical studies off southeast Africa indicate large areas of thinned continental or transitional crust; palaeomagnetic studies show that the western side of Madagascar lay alongside equatorial East Africa; and from the pattern of sea-floor spreading between Madagascar and India we deduce that the southern half of the western margin of India cannot have lain, as customarily shown, alongside the eastern margin of Madagascar, but must have lain farther south. This information about Madagascar provides the crucial link between East (Antarctica, Australia, India) and West (South America, Africa) Gondwanaland. The rest of East and West Gondwanaland is brought into contact so that the Falkland Plateau opposes the margin of Antarctica between 10° and 15°E and the southern part of South America fits without deformation into the Weddell Sea re-entrant of Antarctica. In terms of the continuity of geological features and the cluster of pre-break-up palaeomagnetic poles, the revised fit is at least as favourable as that of Smith and Hallam (1970). In its close match of the continental outlines and its harmony with the pattern of subsequent sea-floor spreading, the revised fit is superior to previous reconstructions.